Hubungan Indeks Massa Tubuh dengan Kadar Kolesterol Total pada Staf dan Guru SMA Negeri 1 Kendari - Nur Rahma Musadalifa; Satrio Wicaksono; Tien Tien (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACT Background:The nutritional status of adults can be monitored by using the body mass index of nutritional status especially that associated with excess weight and less weight. Overweight can also affect cholesterol levels in the body which is one of the most important factors for determining a person's risk of developing cardiovasculardisease. Research Purposes: The purpose of this research is to know the relationship between body mass index with total cholesterol levels of staff and teachers at SMAN 1 Kendari.Research Methods:This research was an analytic observational study with cross-sectional design. The study population was the entire staff and teachers of SMAN 1 Kendari as many as 103 people. The method used in sampling was total sampling. The number of samples were 51 people. This research was conducted with the approval of spread sheets and questionnaires, measuring height and weight, then measures the total cholesterol level. Data were analyzed using Pearson correlation test. It was considered significant at p value ≤0,05. Research result:The results obtained of this research were the staff and teachers who had a unnormal body mass index as much as 42 respondents (82.3%) and who had normal body mass index by 9 respondents (17.6%). Total cholesterol levels in the staff and teachers gained as much as 20 respondents had normal cholesterol levels (39.2%), as many as 20 respondents had a slightly high cholesterol (39.2%), and as many as 11 respondents had highest cholesterol was (21.6% ). Based on statistical test found that there was a significant relationship between body mass index with total cholesterol (p = 0.001).Conclusion: The Conclusions from this research was there were relationship between body mass index with total cholesterol levels of staff and teachers at SMAN 1 Kendari.Keywords: Body mass index, total cholesterol levels, staff and teachers SMAN 1 Kendari.